A Foil Flip-Chip Interconnect With an Ultra-Broadband Bandwidth of 130 GHz and Beyond for Heterogeneous High-End System Designs - Pfahler, Tim; Scheder, André; Bridier, Anna; Nagel, Mathias; Vossiek, Martin (IEEE Journal of Microwaves, 2024)
This paper presents an ultra-broadband, low-loss, flexible liquid crystal polymer substrate-to-substrate interconnect with a bandwidth of more than 130 GHz. The transition discontinuity was minimized by maintaining both the reference impedance and the electromagnetic field conformity across the transition from alumina substrate to flip-chip foil. Therefore, more than 600 μm long flexible flip-chip interconnects can be realized for bridging millimeter-wave sub-modules and enabling ultra-broadband heterogeneous system design with a measured return loss of above 20 dB. Furthermore, the interconnect can realize ramp interconnections between monolithic microwave integrated circuits or substrates with different substrate heights due to the flexible foil substrate. Minimum parasitic radiation at the transition is realized through a closely spaced signal-to-ground connection. Furthermore, the robustness of the proposed interconnect against lateral misalignment in the assembly is presented through simulation and measurement. An outstanding insertion loss of less than 0.3 dB per transition over a bandwidth of more than 130 GHz is shown.
CRIS-Team Scopus Importer:2024-08-02
Keywords: Assembly; bond-wire; flip-chip; interconnect; liquid crystal polymer (LCP); measurement and test; monolithic microwave integrated circuit (MMIC); packaging; permittivity; signal transition; surface roughness; system-in-package; transition characterization